The therapeutic use exemption under the Wada code: Balancing medical necessity against the right to clean sport - Greenwood, M. (James Cook University Law Review, 2019)
The World Anti-Doping Agency ('WADA') is responsible for promoting, coordinating and monitoring anti-doping in elite sport. While it is necessary for WADA to protect athletes' right to participate in doping-free sport, the health of all athletes must not be compromised by prohibiting medical treatment entirely. WADA's Therapeutic Use Exemption ('TUE') recognises an athlete's legitimate therapeutic need for treatment which would otherwise be banned. Following the September 2016 hacking of WADA's databases containing confidential athlete medical data, WADA's TUE regime was widely criticised for the high number of elite athletes requiring TUEs. In light of such concerns, this paper evaluates the WADA's TUE regime. While the TUE regime largely balances competing interests of clean sport with athlete wellbeing, there is room for improvement. The author recommends changes to the current TUE application process to increase fairness to applicants and promote transparency, stringent regulation and training of sporting physicians, greater supervision and education of athletes granted TUEs, and greater transparency surrounding TUE disclosure. With the 2021 World Anti-Doping Code Review well underway, the current TUE regime must be carefully considered by sporting stakeholders to ensure positive changes can be made to WADA's TUE regime.